Power Moves Beyond Complementarity: A Staring Look Elicits Avoidance in Low Power Perceivers and Approach in High Power Perceivers. (August 2017) - Weick, Mario; McCall, Cade; Blascovich, Jim
Sustained, direct eye-gaze—staring—is a powerful cue that elicits strong responses in many primate and nonprimate species. The present research examined whether fleeting experiences of high and low power alter individuals' spontaneous responses to the staring gaze of an onlooker. We report two experimental studies showing that sustained, direct gaze elicits spontaneous avoidance tendencies in low power perceivers and spontaneous approach tendencies in high power perceivers. These effects emerged during interactions with different targets and when power was manipulated between-individuals (Study 1) and within-individuals (Study 2), thus attesting to a high degree of flexibility in perceivers' reactions to gaze cues. Together, the present findings indicate that power can break the cycle of complementarity in individuals' spontaneous responding: Low power perceivers complement and move away from, and high power perceivers reciprocate and move toward, staring onlookers.